2021
DOI: 10.1088/1361-6595/ac14a8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field stabilization of low current DC arc discharge in cross flow in argon gas at atmospheric pressure—a numerical modelling study

Abstract: In this work we study the effect of an external magnetic field and gas flow on the properties of a low current DC (gliding) arc discharge in argon at atmospheric pressure. We consider a cross flow configuration, in which argon gas flows perpendicularly to the arc current, while the external magnetic field is perpendicular to both the arc current and the gas flow. The study is based on a 2D numerical fluid plasma model of the discharge, coupled with a gas flow model based on the Navier-Stokes equations and a ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…We were also able to show that the results from this study match the predictions in [5]. The simulation results from [5] give us an estimate for the arc parameters in the case of a laminar flow under similar conditions. The predicted behavior of the arc-to-wall attachment matches our experimental observations.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…We were also able to show that the results from this study match the predictions in [5]. The simulation results from [5] give us an estimate for the arc parameters in the case of a laminar flow under similar conditions. The predicted behavior of the arc-to-wall attachment matches our experimental observations.…”
Section: Discussionsupporting
confidence: 73%
“…The conditions here correspond to the case of a 4-mm distance between the dielectric glasses in [5]; qualitatively, the discharge in the experiments shows the same behavior -the arc is stabilized near one of the dielectric walls and not in the middle. In [5], it is shown that the increase in the gas velocity, i.e., the gas flow, leads to a decrease in the gas temperature, a thinner arc column (reduced radius) and to the effect mentioned whereby the arc gets pushed to one of the side walls. These effects can lead to the conversion reduction seen in figure 3 (a) in several ways: i) the arc column has a smaller crosssection in the flow direction, so that a lesser amount of gas passes through it and therefore less of the gas is treated, ii) the gas that enters the arc column remains in the arc region for a shorter time, iii) the near arc region has a lower average temperature.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations